Changes in the level of selected condition abilities of youth soccer players - Tvrdy, M.; Lednicky, A.; Peracek, P.; Obetko, M.; Babic, M. (Journal of Physical Education and Sport, 2020)
The demands on a player during the match constantly increase in all areas, including the condition area. This research aimed to point out the changes in the level of selected condition abilities (speed, strength and endurance) of youth soccer players due to the 8-week winter preparation period. We assumed that due to the 8-week winter preparation period, there would be significant changes in the level of selected condition abilities (speed, strength and endurance) of youth soccer players. The research group consisted of elite players (n=13) in the U14 age category. The average age of this group during this research was 13.83 ±0.21 years. To find out the level of selected displays of condition abilities (speed, strength and endurance), we used a battery of three tests: 20-m sprint test, Counter-movement jump test (CMJ) and Yo-Yo Intermittent recovery test level 1 (YIRT1). We used Wilcoxon signed-rank test (p < 0.05) and Cohen´s "r" (effect size) to find out the significanceof differences in the resultant values of the test of selected condition (speed, strength and endurance) abilities.We found out that players improved significantly (p < 0.01) in all selected condition abilities (speed, strength and endurance). We recommend incorporating to the training process the training stimuli more often (specific and non-specific) to develop the speed abilities. We recommend incorporating more exercises for the developmentof explosive power of lower limbs (plyometric training) into training units not only in the preparatory period. In terms of endurance abilities, considering the huge differences found in the YYRT1 test, we would recommend a differentiated development of endurance abilities using intermittent methods, which are specific for soccer.